Penggunaan Metode Pavement Condition Index (PCI) dan Present Serviceability Index (PSI) dalam Penilaian Kerusakan Jalan di Kota Palu (Studi Kasus : Jalan Karanja Lembah, Kota Palu) - M. Sutrisno; M. Mashuri; I. Mashuri; A. Natalin (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2023)
Street of Karanja Lembah is a provincial road linking Palu City and Sigi Regency. After a visual survey, the road has suffered a lot of damage, especially on its surface. The purpose of this study was to determine the pavement condition values based on the Pavement Condition Index (PCI) method and the Present Serviceability Index (PSI) method, as well as to determine the type of road handling based on the PCI and PSI values obtained on these roads. The PCI method is carried out directly by dividing the road into several segments called segment units, then recording the type of damage, the dimensions of the damage, and the severity of the damage for each type of damage. In research using the PSI method, the PSI value was calculated using IRI (International Roughness Index) data obtained from the Highways Service of Central Sulawesi Province. From the results of the analysis, it was obtained that the average PCI value for Jalan Karaja Lembah was 79.95% with a "very good" pavement condition, while the average PSI value for Jalan Karaja Lembah was 2.13% with a pavement condition "moderate". For the right type of handling for the PSI and PCI methods, namely the type of periodic maintenance.